Fluorescein Leakage and Optical Coherence Tomography Angiography Features of Microaneurysms in Diabetic Retinopathy - Ruoyu Chen; Anyi Liang; Jie Yao; Zicheng Wang; Yesheng Chen; Xuenan Zhuang; Yunkao Zeng; Liang Zhang; Dan Cao (Journal of Diabetes Research)
Background and Objective. To correlate optical coherence tomography angiography (OCTA) characteristics of diabetic microaneurysms (MAs) with leakage status on fluorescein angiography (FA). Patients and Methods. 167 MAs from 39 diabetic eyes were analyzed using OCTA and FA simultaneously. The characteristics of MAs on OCTA en face, OCT en face, and OCT B-scan with flow overlay were evaluated and correlated with fluorescein leakage status. Results. Thirty-six, fifty-two, and seventy-nine MAs showed no, mild, and severe leakage on FA, respectively. Most MAs (61.7%) were centered in the inner nuclear layer. Cystoid spaces were observed adjacent to 60 (35.9%) MAs. MAs with severe leakage had a statistically higher flow proportion compared to MAs with no or mild leakage (both P<0.001). Only 112 MAs (67.1%) were visualized in the OCTA en face images, while 165 MAs (98.8%) could be visualized in the OCT en face images. The location of MAs did not associate significantly with FA leakage status. The presence of nearby cystoid spaces and higher flow proportion by OCT B-scan with flow overlay correlated significantly with FA leakage status. Conclusion. The flow proportion of MAs observed on OCT B-scans with flow overlay might be a potential biomarker to identify leaking MAs. A combination of OCT B-scan, OCT en face, and OCTA en face images increased the detection rate of diabetic MAs in a noninvasive way.